MIGA Annual Report 2019 - Multilateral Investment Guarantee Agency (Washington, DC: Multilateral Investment Guarantee Agency, 2019)
Private investors provide not just financing, but also solutions, for projects in developing countries. Yet, non-commercial risks can make them hesitant to invest in developing countries. A member of the World Bank Group, MIGA is committed to strong development impact and promoting projects that are economically, environmentally, and socially sustainable. MIGA helps investors mitigate the risks of restrictions on currency conversion and transfer, breach of contract by governments, expropriation, and war and civil disturbance, and also offers credit enhancement. Over the last six years, MIGA has doubled its portfolio, resulting in approximately 50 million people gaining access to power, and $3.9 billion in annual taxes and fees paid to host governments through MIGA-supported projects.